Molecular identification of pollen donor plants on a progeny of Cambona-4 female matrix of maté (Ilex paraguariensis St. Hil. – Aquifoliaceae) - DOI: 10.4025/actascibiolsci.v32i1.764 (Acta Scientiarum. Biological Sciences, 2009)
A progeny of Cambona-4, a female maté plant (Ilex paraguariensis) selected by its agronomical characteristics and mild flavor, was evaluated using RAPD markers in order to identify its male parents. Using RAPD markers specifics of each one of the four potential males, the paternity of 84 out of 107 offsprings was confirmed. The majority of the offsprings (83.3%) were ascribed to pollen donor A, while male plants B, C, and D represented 11.9, 4.8, and 0%, respectively. The highly desirable agronomical characteristics and product quality of Cambona-4/pollen donor A offsprings, identified by RAPD markers, lead to the planting of an orchard Cambona-4 and pollinator A to obtain bi-clonal commercial seeds.